Предмет: Алгебра,
автор: psorokina117
Алгебра! прошу помогите! даю 100 балов
Приложения:
Ответы
Автор ответа:
0
Ответ:
Объяснение:
Автор ответа:
0
Объяснение:
а² + (3а² - а + 7) + (-а² + 9а - 4) =
а² + 3а² - а + 7 - а² + 9а - 4 =
(а² + 3а² - а²) + (-а + 9а) + (7 - 4) = 3а² + 8а + 3
-mn - (2mn + n² - m) - (-4mn - 2n² + 5m) =
-mn - 2mn - n² + m + 4mn + 2n² - 5m =
(-mn - 2mn + 4mn) + (-n² + 2n²) + (m - 5m) =
1mn + 1n² + (-4m) = mn + n² - 4m
Похожие вопросы
Предмет: Алгебра,
автор: zadoroznukula
Предмет: Оʻzbek tili,
автор: eger666
Предмет: Английский язык,
автор: nureevviktor73
Предмет: Қазақ тiлi,
автор: Аноним
Предмет: Литература,
автор: zanybekalpamys258